Prompting Theory into Practice: Utilizing ChatGPT-4 in a Curriculum Planning Course - Liat Biberman-Shalev (Education Sciences, 2025)
As of late, generative AI tools have been rapidly gaining purchase as an important part of life. Thus, one cannot ignore their growing integration into educational landscapes, including teacher education. This qualitative study examines how pre-service teachers (PSTs) leverage ChatGPT-4 to apply constructivist theory in curriculum planning (CP). The findings revealed three approaches through which PSTs used the chatbot to apply theory to practice: (a) simplifying theory, (b) applying theory, and (c) visualizing theory. The findings suggest that the need to refine prompts using curricular language and engaging in creative and critical thinking supported the translation process. In incorporating ChatGPT-4 into their CP, PSTs considered multiple factors, including ideation, inspiration, creativity, reliability, and insufficient personalization—attesting to a balanced perspective on the use of this tool, i.e., recognizing the potential and benefits of utilizing the chatbot, while remaining cognizant of its associated risks and limitations. This study points to aspects of CP using generative AI, which teacher educators should discuss with PSTs.